2008
DOI: 10.1002/hed.20842
|View full text |Cite
|
Sign up to set email alerts
|

Do neck levels negative on initial CT need to be dissected after definitive radiation therapy with or without chemotherapy?

Abstract: After radiation with or without chemotherapy, neck dissection of an initially negative neck level may not be necessary. Neck dissection may target only initially positive levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Though in a meta-analysis the accuracy of CT to detect cervical node metastases was lower than both ultrasonography (US) and US-guided FNAC [16], CT use is still widespread in daily clinical practice for several reasons, including its accessibility and its relatively straightforward interpretation with low inter-observer variability [16]. Positive cervical nodes on CT are usually defined those with a maximum axial diameter > 10 mm (> 5 mm if retropharyngeal) and/or with internal focal defects, such as irregular enhancement pattern [15]. However, a prospective multi-institutional study on 213 patients failed to show a benefit on both sensitivity and specificity from adding information on internal abnormality to the one on size for nodes 10 mm or smaller in largest axial dimension on CT [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though in a meta-analysis the accuracy of CT to detect cervical node metastases was lower than both ultrasonography (US) and US-guided FNAC [16], CT use is still widespread in daily clinical practice for several reasons, including its accessibility and its relatively straightforward interpretation with low inter-observer variability [16]. Positive cervical nodes on CT are usually defined those with a maximum axial diameter > 10 mm (> 5 mm if retropharyngeal) and/or with internal focal defects, such as irregular enhancement pattern [15]. However, a prospective multi-institutional study on 213 patients failed to show a benefit on both sensitivity and specificity from adding information on internal abnormality to the one on size for nodes 10 mm or smaller in largest axial dimension on CT [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity and specificity vary in relationships with the nodal size cut-off used to define a ‘negative’ scan and they have been reported to be 0.88 and 0.39, respectively, for nodal sizes up to 10 mm in largest axial diameter [14]. While a neck level that does not contain any lymph node exceeding 10 mm is usually considered ‘negative’ [15], we investigated also more restrictive cut-offs: 9 mm (sensitivity: 0.92, specificity: 0.31); 8 mm (sensitivity: 0.95, specificity: 0.22); 7 mm (sensitivity: 0.97, specificity: 0.17); 5 mm (sensitivity: 0.98, specificity: 0.13) [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Posttreatment surgery was considered for bulky, resectable nodes at diagnosis (> 4-4.5 cm) regardless of response or for residual disease [37].…”
Section: Clinical Assessmentsmentioning
confidence: 99%
“…We suspect that the amount of disease present was low, and it would be amenable to being controlled by upfront chemoradiotherapy. In the experience of Rao et al, no tumor was found at pathology in 56 neck levels that had been considered negative on initial pretreatment computed tomography scan and had been electively treated with chemoradiotherapy 11. Moreover, according to Lango et al, pathologic residual disease outside clinically involved areas portends a poor prognosis regardless of ND 22.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were considered to have positive lymph node status by imaging if the lymph nodes met any of the following objective criteria: maximum axial diameter >1 cm, oval/round as opposed to reniform shape, hypodensity suspicious for necrosis, irregular enhancement pattern, and presence of extracapsular penetration 10, 11. Level V encompasses all the lymph nodes contained within the posterior triangle; its boundaries are the anterior border of the trapezius muscle (posteriorly), the posterior border of the sternocleidomastoid muscle (anteriorly), and the clavicle (inferiorly) 9.…”
Section: Methodsmentioning
confidence: 99%